Generation and characterization of two human induced pluripotent stem cell (hiPSC) lines homozygous for the Apolipoprotein e4 (APOE4) risk variant—Alzheimer's disease (ASUi005-A) and healthy non-demented control (ASUi006-A) - Nicholas Brookhouser; Ping Zhang; Richard Caselli; Jean J. Kim; David A. Brafman (Stem Cell Research, 2018)
Although the majority of late-onset Alzheimer's disease (AD) patients are labeled sporadic, multiple genetic risk variants have been identified, the most powerful and prevalent of which is the e4 variant of the Apolipoprotein E (APOE) gene. Here, we generated human induced pluripotent stem cell (hiPSC) lines from the peripheral blood mononuclear cells (PBMCs) of a clinically diagnosed AD patient [ASUi005-A] and a non-demented control (NDC) patient [ASUi006-A] homozygous for the APOE4 risk allele. These hiPSCs maintained their original genotype, expressed pluripotency markers, exhibited a normal karyotype, and retained the ability to differentiate into cells representative of the three germ layers.Resource tableUnlabelled TableUnique stem cell lines identifierASUi005-AASUi006-AAlternative names of stem cell linesASU-161ASU-487InstitutionArizona State University; Tempe, AZ; USAContact information of distributorDavid Brafman, David.Brafman@asu.eduType of cell linesiPSCOriginHumanCell sourceHuman peripheral blood mononuclear cells (PBMCs)ClonalityClonalMethod of reprogrammingCytoTune®-iPS 2.0 Reprogramming SystemMultiline rationaleAge-matched Alzheimer's disease and non-demented control hiPSC lines homozygous for the APOE 4 risk factorGene modificationNoType of modificationN/AAssociated diseaseAlzheimer's diseaseGene/locusApolipoprotein E (APOE)Method of modificationN/AName of transgene or resistanceN/AInducible/constitutive systemN/ADate archived/stock dateMarch 2018Cell line repository/bankNot applicableEthical approvalMayo Clinic Institutional Review Board; IRB # 15-008674